2009
DOI: 10.9775/kvfd.2009.1560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic and Inorganic Selenium Supplementation on Egg Production Parameters and Egg Selenium Content of Laying Japanese Quail

Abstract: Bu çalışma, yumurtacı Japon bıldırcınlarının karma yemlerine organik ve inorganik selenyum (Se) katkısının yumurta verim parametreleri ile yumurta akı ve sarısının Se içeriğine etkilerini belirlemek amacıyla yapılmıştır. Denemede 10 haftalık yaşta 90 adet yumurtacı Japon bıldırcını (Coturnix coturnix Japonica) kullanılmıştır. Bıldırcınlar her birinde 18 hayvan bulunan 5 gruba ayrılmış ve tüm hayvanlar bireysel kafeslerde barındırılmıştır. Gruplardan biri Se katkısız bazal yemle (kontrol), ikinci grup bazal yem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…Payne et al found that average hen-day production is not affected by Se-source, but Seyeast increased the Se egg concentration more effectively than selenite [6]. Canogullari et al reported that the Se levels in egg yolk and egg albumin were higher in Se-supplemented groups compared to unsupplemented controls (p<0.05) and established that organic Se forms were more effective than inorganic Se as supplements [7]. Yaroshenko et al pointed out that supplementation of 0.4 ppm Se to hens resulted in production of Se-enriched eggs with a prolonged period of freshness [8].…”
Section: Introductionmentioning
confidence: 95%
“…Payne et al found that average hen-day production is not affected by Se-source, but Seyeast increased the Se egg concentration more effectively than selenite [6]. Canogullari et al reported that the Se levels in egg yolk and egg albumin were higher in Se-supplemented groups compared to unsupplemented controls (p<0.05) and established that organic Se forms were more effective than inorganic Se as supplements [7]. Yaroshenko et al pointed out that supplementation of 0.4 ppm Se to hens resulted in production of Se-enriched eggs with a prolonged period of freshness [8].…”
Section: Introductionmentioning
confidence: 95%
“…The use of Se-enriched yeast in laying hen diets increases selenium content of egg (Utterback et al 2005;Gajcevic et al 2009;Attia et al 2010). It is further reported that selenium sources help increasing egg production traits as well as fertility and hatchability (Attia et al 2010;Cano gullari et al 2010;Waseem et al 2016). In particular, expansions and commercialisation of organic sources of selenium have originated a new era in the availability of Se-enriched products (Fisinin et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Biological antioxidants, R. Bras. Zootec., 46(2):123-129, 2017 such as vitamin C, vitamin E, and selenium, react with free radicals or precursor metabolites and convert them into less reactive molecules, leading to the delay or prevention of oxidation of biological molecules (Surai, 2007;Baylan et al, 2010). It is increasingly appreciated that diet plays a pivotal role in maintaining animal health, productivity, and reproductive performance of farm animals and poultry.…”
Section: Introductionmentioning
confidence: 99%
“…The need for selenium may change in stress conditions, such as low-protein intake. It is well-documented that dietary selenium supplementation improves feed efficiency, minimizes changes of blood biochemical parameters, elevates antioxidant activities, and decreases lipid peroxidation products in stressed birds (Fan et al, 2009;Canogullari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%